Environmental Enrichment Modulates Drug Addiction and Binge-Like Consumption of Highly Rewarding Substances: A Role for Anxiety and Compulsivity Brain Systems? - Rodríguez-Ortega, Elisa; Cubero, Inmaculada (Frontiers in Behavioral Neuroscience, 2018)
Drug addiction is a chronic disorder comprising components of both impulsivity and compulsivity in the so called “addiction cycle” which develops over time from early non-dependent, repetitive, binge-consumption to later post-dependent compulsive consumption. Thus, frequent binge-like intake is a typical pattern of excessive drug intake characteristic of the pre-dependent phase of the addiction cycle, which represent an important risk factor to develop addiction in vulnerable individuals. In this framework, it is of paramount interest to further understand the earliest stage of the addiction cycle so novel approaches would emerge aimed to control repetitive episodes of binge-consumption in non-dependent subjects, protecting vulnerable individuals from transition to dependence. Environmental enrichment (EE) is a preclinical animal model in which animals are housed under novel, social enriched conditions, which allows exercising and provides sensory and cognitive stimulation. EE promotes important improvements for a variety of cognitive processes and clear therapeutic and protective effects preventing ethanol (EtOH) and drug addiction as well. Interestingly, recent observations suggest that EE might additionally modulate binge-like intake of highly palatable caloric substances, including EtOH, which suggests the ability of EE to regulate consumption during the initial stage of the addiction cycle. We have proposed that EE protective and therapeutic effects on binge-consumption of palatable substances might primarily be mediated by the modulatory control that EE exerts on anxiety and impulsivity/compulsivity traits, which are all risk factors favoring transition to drug addiction